CULTURAL EXTINCTION OF IRAQI MINORITIES: AN ANALYTICAL STUDY - Sabar, Mohammed Ghazi (PT. Antis International Publisher, 2025)
Objective: Cultural diversity in Iraq faces profound existential challenges that threaten the survival of religious and ethnic minority identities. This research analyses the manifestations of cultural extinction through the decline of mother tongues, the erosion of communal rituals, displacement and spatial uprooting, and the weakening of institutional presence among minority groups. Method: The study is grounded in an integrated theoretical framework that incorporates the concepts of cultural hegemony, symbolic violence, forced assimilation, and symbolic annihilation to understand the dynamics of this phenomenon. Results: The findings reveal that cultural extinction is not merely a gradual process of losing symbols but rather a reflection of structural power relations that reproduce symbolic inequalities through institutions such as education, media, the labour market, and religion. These transformations have direct implications for society at large, most notably the erosion of social capital, the fragility of cultural citizenship, the deepening of mistrust between the state and citizens, and the weakening of Iraq’s soft power in international arenas. Novelty: The study concludes that protecting cultural diversity is not only a humanitarian obligation but also a strategic necessity, as the sustainability of national stability requires genuine recognition of minorities, empowerment in decision-making, and safeguarding of their heritage and collective memory within a unifying national framework.